Covered Metal Stenting for Malignant Lower Biliary Stricture with Pancreatic Duct Obstruction: Is Endoscopic Sphincterotomy Needed? - Kazunari Nakahara; Chiaki Okuse; Keigo Suetani; Yosuke Michikawa; Shinjiro Kobayashi; Takehito Otsubo; Fumio Itoh (Gastroenterology Research and Practice)
Aims. To evaluate the need for endoscopic sphincterotomy (EST) before covered self-expandable metal stent (CSEMS) deployment for malignant lower biliary stricture with pancreatic duct obstruction. Methods. This study included 79 patients who underwent CSEMS deployment for unresectable malignant lower biliary stricture with pancreatic duct obstruction. Treatment outcomes and complications were compared between 38 patients with EST before CSEMS deployment (EST group) and 41 without EST (non-EST group). Results. The technical success rates were 100% in both the EST and the non-EST group. The incidence of pancreatitis was 2.6% in the EST, and 2.4% in the non-EST group (). The incidences of overall complications were 18.4% and 14.6%, respectively, (). Within the non-EST groups, the incidence of pancreatitis was 0% in patients with fully covered stent deployment and 3.6% in those with partially covered stent deployment (). In the multivariate analysis, younger age (, OR 12) and nonpancreatic cancer (, OR 24) were significant risk factors for overall complications after CSEMS deployment. EST was not identified as a risk factor. Conclusions. EST did not reduce the incidence of pancreatitis after CSEMS deployment in patients of unresectable distal malignant obstruction with pancreatic duct obstruction.